A Feasibility Study For The Investment Project On Battery Production Industry - Armaneri, Özgür (Afyon Kocatepe Üniversitesi, 2007)
The investment projects are one the most important tools of economic development. In general, the investment project is defined as the suggestions made for creating new opportunities expansion and development with the aim of increasing the production of goods and services in a specific time period. So, they have to be analyzed very carefully before they are realized. Feasibility study is the most important part of the techno-economic, financial and economic analyses of the investment project. The aim of this paper is to propose a systematic project analysis process and by using this process to conduct a feasibility study in a real investment project on battery production industry.

Yatırım projeleri, ekonomik kalkınmanın en önemli araçlarından biridir. Genel anlamda yatırım projesi, belirli bir zaman süresi içinde, mal ve hizmetlerin üretimini arttırmak için, bazı olanaklar yaratma, genişletme ve geliştirmeye yönelik öneriler olarak tanımlanabilir. Dolayısıyla, yatırım projeleri gerçekleştirilmeden önce çok dikkatli bir şekilde analiz edilmelidirler. Fizibilite etüdü, yatırım projelerinin tekno-ekonomik, finansal ve ekonomik analizlerinin en önemli bölümüdür. Bu makalenin amacı, sistematik bir proje analiz süreci sunmak ve bu süreci kullanarak akü üretim endüstrisindeki gerçek bir yatırım projesi üzerine fizibilite etüdü yapmaktır.
Akü Üretim Endüstrisinde Bir Yatırım Projesi İçin Fizibilite Çalışması
Keywords: Feasibility Study, Investment Projects, Project Management